Identification and reduction of unwanted stray radiation using an energy- and position-sensitive Compton polarimeter. (26th November 2015) - Blumenhagen, K-H; Spillmann, U; Gaßner, T; Gumberidze, A; Märtin, R; Schell, N; Trotsenko, S; Weber, G; Stöhlker, Th
Abstract: In this work, we report on an experiment that investigated the elastic scattering of linearly polarized 175 keV photons on a gold target. A combined measurement of the angular distribution and the linear polarization of the scattered photons was performed using standard germanium detectors and a double-sided Si(Li) strip polarimeter. Since the data analysis is still in progress, we will show results in forthcoming papers and present here how the polarimeter was used to identify a lack of shielding during the experiment.